Maskulinitas dalam Iklan Makeup BarenBliss "Gabriel Prince as a Makeup Muse" - Putri, Ayudya; Ririn Puspita Tutiasri (Jurnal Dakwah dan Komunikasi, 2024)
In this day seeing men wearing cosmetics is no longer a novelty. Makeup is not just for beautifying women. The genderless beauty advertising concept used by BarenBliss "Gabriel Prince as a Makeup Muse" is an idea that goes against the stereotype of all beauty or self-care products always sticking to one gender, namely women. Descriptive qualitative research using the theory of individual differences. Research data was obtained through interviews with informants. The results of this study show different perceptions, namely that the advertisement is new and dares to appear different from other advertisements because it uses a male model in the advertisement, while other informants consider that this advertisement is not suitable if played by a male model. informants have the opinion that the form of masculinity in the advertisement can be seen from the concept of the advertisement that makes Gabriel Prince as a male model dare to take different steps by using makeup. The masculinity depicted in the BarenBliss advert is also seen through the style of dress. However, one informant disagreed with the masculinity in the advert because makeup is identic with women. These perceptions are created because young men and young women are influenced by different backgrounds, knowledge, experiences, and lifestyles.